Eigenvalue Placement by Quantifier Elimination - the Static Output Feedback Problem - Röbenack, Klaus; Voßwinkel, Rick (Acta Cybernetica, 2020)
This contribution deals with the static output feedback problem of linear time-invariant systems. This is still an area of active research, in contrast to the observer-based state feedback problem, which has been solved decades ago. We consider the formulation and solution of static output feedback design problems using quantifier elimination techniques. Stabilization as well as more specified eigenvalue placement scenarios are the focus of the paper.